VISIONARY LEADERSHIP AND CRISIS MANAGEMENT IN EDUCATION: SECONDARY SCHOOLTEACHERS' PERSPECTIVE - Ermis, Sermin Agrali; Dereceli, Ebru; Toros, Turhan; Serin, Emre; Kara, Tayfun; Uzun, Meliha (Unesp-Faculdade Ciencias & Letras, 2025)
This study examines the visionary leadership and crisis management skills of teachers, key figures in students' lives, across three groups: Verbal (Turkish, Social Studies, Foreign Languages), Numerical (Mathematics, Science), and Social (Physical Education, Music, Art). The aim was to assess their levels of visionary leadership and crisis management, analyze the relationship between them, and identify differences based on specific variables. Using a survey model, data were collected from 303 teachers (151 male, 152 female) selected through stratified sampling. The participants' average age and years of service were homogeneously distributed. Two instruments were applied: the Visionary Leadership Scale (Sashkin, 1996; adapted by Tanr & imath;bil, 2015) and the Crisis Management Scale (& Ccedil;al & imath;& scedil;kan, 2020). Data analysis involved Kolmogorov-Smirnov, t-test, two-way ANOVA, and Pearson correlation tests. Results showed low levels of visionary leadership and crisis management. However, a strong, positive correlation was found between these two competencies, indicating mutual influence.
Keywords: Leader; Visionary Leadership; Crisis Management; Crisis Lea-Teacher